Children's awareness of ethnic outgroup symbols: Piloting a task in the Republic of Ireland - Dearbháile Counihan; Sarah Carol; Laura K. Taylor (International Journal of Psychology, 2022)
Exploring children's awareness of social categories could uncover the foundation of intergroup attitudes and behaviours. Indigenous to Ireland, Travellers are an ethnic minority marked by a tradition of nomadism, only formally recognised as a distinct ethnic group in 2017. This brief report analyses data from 148 children aged 6–12 (55% female) in the Republic of Ireland. A quantitative task was adapted and applied to assess children's awareness of symbols associated with the Traveller community. We found that primary school children could accurately categorise the symbols which relied on perceptually obvious markers of Traveller identity, and that this remained stable across middle childhood. However, children did not correctly categorise symbols related to less observable elements (e.g., language, trade, religion). To the best of our knowledge, these findings are the first to identify specific symbols which are salient in children's awareness about this marginalised group. Implications for school-based interventions are discussed.
Keywords: 300; children; ethnic awareness; marginalised group; travellers; Ireland